Influence of nickel boride additions on sintering behaviors of injection moulded 17-4 PH stainless steel powder - (:unkn) unknown (My University, 2005)
Effect of nickel boride additions on sintering behavior of injection molded 17-4 PH stainless powder. With increases nickel boride amount, sintering time and temperature, relative density and mechanical properties of specimens increase. Sintering to full density was obtained with the addition of 1 wt.% NiB at 1280°C for 45min. © 2004 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: 17-4 PH stainless steel; Powder injection moulding; Sintering